2018
DOI: 10.3390/su10072461
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Valuation of Urban Forest Attributes in Highly Developed Urban Environments: An Experimental Study Using a Conjoint Choice Model

Abstract: Abstract:It is important to integrate user preferences and demands into the design, planning, and management of urban forests. This is particularly important in highly urbanized areas where land is extremely limited. Based on a survey with 600 participants selected by quota sampling in Seoul, Korea, we developed a conjoint choice model for determining the preferences of urban dwellers on urban forest attributes, the levels of attributes, and the preferences for particular attributes. Then, the preferences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…To acquire such specific information of UGS attributes, the conjoint choice model may be beneficial because it is able to make direct predictions on choices of respondents in the form of a logit model by calculating the part-worth of attribute levels obtained from choice-type data [144]. For example, Hong et al [97] found that the primary salient attributes affecting whether people visit urban forests were forest type, paving material of trail, topography, and travel time from home. At the same time, they were able to specify attribute levels for each forest attribute preferred by forest visitors.…”
Section: Effects Of Motivation and Constraintmentioning
confidence: 99%
See 1 more Smart Citation
“…To acquire such specific information of UGS attributes, the conjoint choice model may be beneficial because it is able to make direct predictions on choices of respondents in the form of a logit model by calculating the part-worth of attribute levels obtained from choice-type data [144]. For example, Hong et al [97] found that the primary salient attributes affecting whether people visit urban forests were forest type, paving material of trail, topography, and travel time from home. At the same time, they were able to specify attribute levels for each forest attribute preferred by forest visitors.…”
Section: Effects Of Motivation and Constraintmentioning
confidence: 99%
“…Particularly, it is an urgent issue for highly urbanized regions and countries. For example, in Korea, where approximately 90% of the population resides in urbanized areas, the Korean government and local authorities have been continuously trying to provide more urban green spaces for years to meet the increasing demand [95][96][97].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies show preference for mixed forest but then deciduous forest usually takes precedence over coniferous. Hong et al [48] and Abildtrup et al [21] have determined a significant preference for broadleaved and mixed forests over coniferous forests among the urban population of Seoul (Korea) and France. In the study review by Ciesielski and Stereńczak [24], central Europeans expressed preference for mixed forests with a higher share of coniferous trees.…”
Section: Forest Type and Structurementioning
confidence: 99%
“…(6) Urban forests also provide various ecosystem services such as microclimate improvement, atmospheric cleanup, (7) energy saving, (8) rainwater collection and storage, the improvement of biological diversification, (9) and the enhancement of soil fertilization; (10) ecological benefits such as noise reduction, landscape beauty and amenity, and recreation and learning; (11) esthetic/welfare benefits such as health improvement; (12) and socioeconomic benefits such as real estate and property value increase. (13) The ecosystem service that is extremely important for our lives is carbon storage and uptake by vegetation; this plays a particularly important role in the alleviation of climate change, the severity of which has been realized only in recent decades. (14,15) Climate change has come to the fore as the most serious environmental issue globally.…”
Section: Introductionmentioning
confidence: 99%